(3GdeYjGQ GdeYQH hGdLGeY GdeZQH Yf aJGhi YdeGA EaQjbjI hGdCfOdS hGdeZQHs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s
(3ChdgG (B:s
(3jHOC HHGH fhGRd GdeYGhVGJ hGdHjhY s
(3BNQgG (B:s
(3habg Gddg JYGdi jYJeO ef jba YdjgG ef GdaVdGA GdCNjGQ GfJgi GdSaQ GdKGdK ef GdfhGRd HMeO Gddg JYGdi hMSf Yhfg s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdc (B90) s
Keywords: (3Gdabg GdeGdcjs